The Effect of Love of Money and Intrinsic Religiosity on the Tendency of Village Fund Accounting Fraud - Marce Sherly Kase; Natalia Lily Babulu (International Journal of Science and Society, 2023)
This study focuses on measuring the level of love of money and intrinsic religiosity of village officials that have an impact on village fund accounting fraud. This study aims to (1) determine the effect of love of money on the tendency of village fund accounting fraud (2) determine the effect of intrinsic religiosity on the tendency of village fund accounting fraud (3) determine the effect of love of money and intrinsic religiosity on the tendency of village fund accounting fraud. The analytical tool used in this research is multiple linear regression. Data were collected through observation, interviews and questionnaires. The population of this research is the village apparatus of West Insana and Central Insana sub-districts of North Central Timor Regency. The number of samples in this study were 54 people. The results of this study indicate that love of money has a positive effect on the tendency of village fund accounting fraud and Intrinsic Religiosity has a negative effect on the tendency of village fund accounting fraud.